A New Fluorescent Sensor for Arsenic(III) Determination in Aqueous Media - (:unkn) unknown (JAPAN SOC ANALYTICAL CHEMISTRY, 2020)
A novel polymeric membrane sensor was developed by using 2-hydroxyethyl acrylate, trimethylolpropane triacrylate, (3-mercaptopropyl)trimethoxysilane, and poly(ethylene glycol)diacrylate for As(III) determination. Various parameters, like the pH, response time, the foreign ions, and concentration effects were investigated for deciding the optimum working conditions of the polymeric sensor. As a result of this investigation, the optimum pH was found to be 2, and the response time was found to be 30 s. The linear range of the sensor was 6.65 x 10(-9) - 3.99 x 10(-8) mol L-1 (0.50 - 2.99 mu g L-1) with a detection limit of 2.33 x 10(-9) mol L-1 (0.18 mu g L-1). Soy flour and well-water samples were successfully analyzed with the developed sensor. The sensor can be used at least 100 times after regeneration. It could be reused by washing with purified water and showed good stability for 6 months.
Keywords: As(III); polymeric membrane; sensor; fluorimetry; STRIPPING VOLTAMMETRIC ANALYSIS; WATER SAMPLES; COLORIMETRIC DETECTION; NANOPARTICLES; SPECIATION; ELECTRODE; FILM